THE REPUBLIC OF UZBEKISTAN IN THE WORLD MAP. MINERAL AND ROW RESOURCES OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Baydullayeva Gulrux Shuxrat qizi (TADQIQOTLAR.UZ, 2024)
Annotation:This article delves into the geographical and geological significance of the Republic of Uzbekistan, shedding light on its rich mineral and raw material resources. Through detailed analysis and exploration, the piece highlights Uzbekistan's position on the world map in terms of its resource wealth. Readers will gain insights into the diverse range of minerals found in Uzbekistan, including gold, copper, uranium, and more, and understand the country's potential as a key player in the global resource market. The article provides a comprehensive look at how Uzbekistan's mineral and raw material resources contribute to its economy and shape its role in the international arena.